THE IMPACT OF INTRODUCING CARBON BOOST TOWARDS THE GROWTH PERFORMANCE AND LIPID ACCUMULATION OF MICROALGAE - TAN, WHITNEY WEE NEE (2021)
Carbon dioxide is an important element for microalgae growth processes, such as photosynthesis and carbon dioxide fixation. However, these vital processes can be restricted by the slow carbon dioxide medium mass transfer.